The risk factors for oral mucositis and the effect of cryotherapy in patients after the BEAM and HD-l-PAM 200 mg/m(2) autologous hematopoietic stem cell transplantation - Vokurka, Samuel; Bystricka, Eva; Scudlova, Jana; Mazur, Ewa; Visokaiova, Maria; Vasilieva, Elizabeth; Brandejsova, Renata; Chvojkova, Ivana; Vrabcova, Martina; Vitkova, Jitka; Mjartanova, Dagmar; Vodickova, Marcela; et al. (European journal of oncology nursing, 2011)
PURPOSE: Oral mucositis (OM) still represents a significant complication of hematopoietic stem cell transplantations (HSCT). Observational studies focusing on risk factor definitions are still warranted. METHOD: A total of 126 patients participated in this observational study after autologous HSCT with the BEAM and HD-l-PAM 200mg/m(2) conditioning regimens. Basic clinical and laboratory variables and their impact on OM were assessed. RESULTS: Age, gender, body mass index, and baseline absolute neutrophil counts were not shown to have any negative impact on OM development. The multivariate analysis revealed oral cryotherapy non-provision as being the most significant predictor for OM incidence (p < 0.0001), followed by BEAM conditioning regimen (p = 0.007), OM in a patient's history (p = 0.002) and lower number of days since the last chemotherapy (p = 0.025). The cryotherapy was remarkably effective both in the single high-dose melphalan 200mg/m(2) conditioning regimen (18% OM in cryotherapy vs. 68% without it, p<0.0001) and in the multidrug BEAM (melphalan 140mg/m(2)) regimen (38% vs. 86%, p=0.006). CONCLUSION: Oral cryotherapy should be implemented into supportive care management in patients treated with high-dose melphalan short-infusion chemotherapy. Large and well-designed randomized trials are necessary to obtain more significant and reliable results and understanding regarding OM risk factors.
Keywords: rozvrh dávkování léků; dospělí; Melphalan; vztah mezi dávkou a účinkem léčiva; Female; karmustin; Adult; výsledek terapie; ženské pohlaví; mladý dospělý; cytarabin; stomatitida; Adolescent; lidé; Hematopoietic Stem Cell Transplantation; autologní transplantace; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Stomatitis; Drug Administration Schedule; Treatment Outcome; Transplantation Conditioning; Antineoplastic Combined Chemotherapy Protocols; Cytarabine; kryoterapie; protokoly protinádorové kombinované chemoterapie; Risk Factors; melfalan; Dose-Response Relationship, Drug; etoposid; prospektivní studie; Male; Aged; Prospective Studies; Cryotherapy; Young Adult; Carmustine; rizikové faktory; lidé středního věku; senioři; mužské pohlaví; Transplantation, Autologous; Etoposide; Middle Aged; mladiství; Humans